ChemInform Abstract: Diphenylprolinol Silyl Ether‐Derived Thioureas as Highly Efficient Catalysts for the Asymmetric Michael Addition of Aldehydes to Nitroalkenes. Issue 39 (September 2015) - He, Chunyan; Ren, Xiaochen; Feng, Yingle; Chai, Yonghai; Zhang, Shengyong; Chen, Weiping
Abstract It is found that the spatial placement of the C‐4 substituent on the pyrrolidine ring of the catalyst has high influence on the reactivity, diastereoselectivity, and enantioselectivity.